Assessment of Impact of Sewage, Industrial Drains and Juke Piles on Krishna River Canal Networks using MATLAB in Vijayawada, Andhra Pradesh, India. - et. al., T. Preethi Rangamani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A systematic study was carried out to assess the water quality at downstream of Krishna river canal networks, which are now facing a severe problem of pollution in Vijayawada. Deterioration of Krishna River canal networks was observed because of the disposal of untreated municipal and industrial sewage through various sewers. During the field visit and sample collection, we observed that time and money for labour force and huge investments for chemicals were needed for continuous sampling laboratory work. Literature reviews state that using systems analysis techniques to plan water pollution control is the foundation for water quality management. Here an attempt was made to develop a water quality model for Krishna River canal networks in Vijayawada by applying Quadratic regression using curve fitting in MATLAB. The result showed that the stimulation is well with the analytical observation, and this model can be used to study other parameters, as well as to reduce the time for laboratory analysis.